Severity of symptoms, physical functioning and satisfaction in patients with lumbar spinal stenosis: a validation study of the Iranian version of the Swiss Spinal Stenosis Score - Azimi, P; Ghandehari, H S; Sadeghi, S; Azhari, S; Aghaei, H N; Mohmmadi, H R; Montazeri, A (Journal of neurosurgical sciences, 2014)
A common cause of low back pain is lumbar spinal stenosis (LSS). The Swiss Spinal Stenosis Score (SSS) is a well-known questionnaire that measures the severity of symptoms, physical functioning and patient's satisfaction in lumbar spinal stenosis. This study aimed to translate and validate the SSS in Iran. A prospective clinical validation study was performed. Forward-backward procedure was applied to translate the original questionnaires into Persian. A sample of patients with lumbar spinal stenosis completed the questionnaire twice: at pre- and postoperative (6 months follow-up) assessments. To test reliability the internal consistency was assessed by the Cronbach's alpha coefficient. Validity was evaluated using the known groups comparison. In addition the Oswestry Disability Index was used to perform convergent validity. In all 121 patients were entered into the study. The mean age of patients was 62.3 (SD=10.2) years. The Cronbach's alpha coefficient for the SSS was 0.88. Validity was performed by known groups analysis and showed satisfactory results. The instrument discriminated well between the subgroups of patients who differed in age, severity of lumbar spinal stenosis, and the Self-Paced Walking Test (SPWT). The change in the Oswestry Disability Index strongly correlated with the change in patients' scores on the SSS; lending support to its good convergent validity (r=0.82; P<0.001). The Iranian version of Swiss Spinal Stenosis Score performed well and the findings suggest that it is a valid measure of symptoms, physical functioning and satisfaction among patients with lumbar spinal stenosis.